Kesiapan Pembelajaran Daring Perspektif Geografis - Darojaturroofi'ah Sodiq; Megarizki Hotmauli; Raudatul Jannah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
Readiness is one of the factor in learning principal that effects the learning process. By the existence of the covid 19, online learning becomes popular in every learning institution nowdays. During the process,it is necessary to know how far the students ready in facing the learning process, not only students in the village but also in the city. Online learning readiness is defined as the time management, independent learning management, having intrinsic motivation, and understanding the way and the experience in independent learning (P. J. Smith, 2005). This research is a quantitative research by focusing on differentiation for collecting the data, the researcher used questionnaire. The readiness in doing the online learning survey is used in collecting the data. The instrument that is used in this research is online learning readiness scale (OLRS) indonesian version instrument (Hidayat, n.d). The survey asked the students to report their characteristic based on the five dimension that is used by (Hung et, al., 2010) such as self-directed learning, motivation for learning, learner control, computer and internet self efficacy and online communication self-efficacy. In analyzing, the technique that is used in this research is Mann-Whitney test (differentiation nonparametric test). Of the 190 research responden the results obtained that the value of Z = -0.802 with a sig. <0.05 which was processed using IBM SPSS Statistics 20.